Sistem Pakar Deteksi Kerusakan Laptop Dengan Metode Forward Chaining - Murjiyanto krisno; Elfira Umar; Agustina Purnami Setiawi (CV. ITTC INDONESIA, 2023)
STIMIKOM Stella Maris Sumba is a high school of informal engineering where many computers or laptops have been damaged, In order to make it easier for laburaturium to check for damage to the computer or to the laptop, research has been picked up on the link between computer malfunctions and the method the author used in this study is forward chaining.An analysis based on research that the obstacles experienced are the technicians having trouble coping with the damage to the laptop, whether it's damage to hardware or the software from research, so that the experts are able to diagnose damage on laptops or computers can make it easier for the laboraturium to do fast diagnostic damage, precise and efficient.The implementation of the design of the diagnostic system on this laptop or computer certainly has a great impact on the campus without any further difficulty diagnosing the damage on the laptop or computer and